Saúde e qualidade na velhice : a percepção do idoso mais velho - Carvalho, Rennata Silva (2012)
Currently there is a significant growth of the elderly population, in absolute and relative numbers highlighting the significant increase of the population aged over 80 years. A recent diagnosis of the elderly population in Brazil found that while the number of elderly is increasing at around 3.5% a year, people over 80 years are increasing 4.7% per year. Given the increasing life expectancy, a phenomenon experienced in developed countries and developing countries, the challenge that presents itself is the maintenance of health and quality of life in individuals with advanced age. The concept of Health and Quality of Life is widely debated and constantly revised, particularly with regard to the elderly population. Therefore research on the conditions under which enjoy good health and quality of life in old age is scientific and social interest. This research aimed to understand the perception of health and quality of life of elderly men over 75 years of age and to investigate and understand old age, including concept, challenges and myths about this process. This dissertation is divided into two articles: the first article consists of a theoretical study and presents a panorama of old age, their characteristics, myths and challenges. The second deals with health and quality of life from the perspective of older men, if those aged over 75 years, as stated.